2004
DOI: 10.1073/pnas.0408007101
|View full text |Cite
|
Sign up to set email alerts
|

Processing of Notch and amyloid precursor protein by γ-secretase is spatially distinct

Abstract: ␥-Secretase activity is associated with a presenilin (PS)-containing macromolecular complex. Whether PS contains the active site of ␥-secretase has been controversial. One challenge is to find PS that is engaged in the active ␥-secretase complex at the cell surface, where some substrates appear to be processed. In this study, we developed an intact cell photolabeling technique that allows the direct visualization of active ␥-secretase at the cell surface. We demonstrated that active ␥-secretase is present in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
74
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(88 citation statements)
references
References 48 publications
13
74
0
1
Order By: Relevance
“…4) (32)(33)(34). Consistent with our sandwich ELISA results, A␤40 was significantly lower in PS1 M146V/ϩ samples compared with wild-type controls (Fig.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…4) (32)(33)(34). Consistent with our sandwich ELISA results, A␤40 was significantly lower in PS1 M146V/ϩ samples compared with wild-type controls (Fig.…”
Section: Resultssupporting
confidence: 89%
“…In Vitro ␥-Secretase Activity-␥-Secretase activity was assayed using a peptide substrate as described (32)(33)(34). Mouse brain membrane proteins were solubilized with 1% CHAPSO and incubated with APP C99.…”
Section: Methodsmentioning
confidence: 99%
“…4, described below) faces the hydrophobic lipid environment. This orientation is consistent with the knowledge that all four component proteins (PS1, Aph-1, NCT, and Pen-2) are integral membrane proteins that can be found together in a proteolytically active complex on the plasma membrane (17,18).…”
Section: Lectin Labeling Identified the Location Of The Nct Ectodomainsupporting
confidence: 91%
“…The g-secretase subunits found in the ER/early secretory pathway most likely represent unassembled or partially assembled subcomplexes, but not the active enzyme. The evidence supporting such a model is manifold and, because of space constraints, only key arguments will be highlighted: (1) APP/C99/C83 are not cleaved by g-secretase in the ER (Cupers et al 2001;Maltese et al 2001;Grimm et al 2003;Kaether et al 2006b); (2) by immuno-electron microscopy, PS1 is not detected in Golgi or TGN but in ER and PM (Rechards et al 2003); whereas the ER pool most likely reflects unassembled PS1, the PM pool has assembled, active complex; (3) only the mature, glycosylated NCT, not immature unglycosylated NCT, is present in the fully assembled, active g-secretase complex Kaether et al 2002), and therefore g-secretase-associated NCTmust have passed the Golgi; (4) g-secretase has been shown by various methods, including cell surface biotinylation, binding of biotinylated inhibitors specific for the active complex, and microscopic techniques, to be present at the PM (Kaether et al 2002;Tarassishin et al 2004;Chyung et al 2005). It has been shown that the 1-cleavage of APP differs in endosomes and PM (Fukumori et al 2006), suggesting that g-secretase has different properties depending on its subcellular localization, maybe because of differences in pH or lipid composition.…”
Section: Subcellular Sites Of G-secretase-mediated App Processingmentioning
confidence: 99%